Miracle At James Towne - Parker, Lois M.; Nang ChanYeema (Washington, D.C. USA Review and Herald Publishing Association, 1984)
A history of the early years of Jamestown, Virginia, with much narrative of the lives of its inhabitants.
Keywords: Adult Nonfiction